Assisted reproductive technique increases the risk of placental polyp. (June 2013) - Baba, Tsuyoshi; Endo, Toshiaki; Ikeda, Keiko; Shimizu, Ayumi; Morishita, Miyuki; Kuno, Yoshika; Honnma, Hiroyuki; Kiya, Tamotsu; Ishioka, Shin-ichi; Saito, Tsuyoshi
Abstract The purpose of this study was to clarify the risk factors and outcomes of placental polyp. This retrospective study was conducted on 1645 patients delivered or aborted in Sapporo Medical University from 2007 through 2011. Transvaginal color Doppler ultrasonography, hysteroscopy, contrast-enhanced MRI or 3D-CT angiography were performed. There were 1532 deliveries and 113 abortions. Seventy-one (4.3%) were ART-conceived and the remaining 1574 (95.7%) were non-ART pregnancies. Fifteen (0.91%) cases were confirmed as having placental polyp. Nine cases of placental polyp were identified among the 1574 (0.57%) as non-ART-related pregnancies, and 6 were identified among the 71 (8.5%) as ART-related pregnancies. Thus, pregnancies achieved through ART showed 20x greater incidence of complicating placental polyp than pregnancies achieved through without ART (p = 9.02 × 10−6; odds ratio, 19.59; 95% confidence interval, 5.27–72.84, logistic regression analysis). Evaluation of blood flow within the polyp showed that in five of seven patients with low blood flow, the polyps spontaneously dropped off 79–115 days postpartum. Thus, ART-related pregnancies may be a risk factor of placental polyp, and spontaneous drop-off of the polyp is often observed in cases with low blood flow within the mass.